Genetic diversity of norovirus genogroup I, II, IV and sapovirus in environmental water in Thailand - Pattara Khamrin (2020)
© 2020 The Author(s) Background: Enteric caliciviruses, including noroviruses (NoVs) and sapoviruses (SaVs) are the most significant pathogens associated with waterborne and foodborne outbreaks of nonbacterial acute gastroenteritis in humans worldwide. Methods: In this study, 126 environmental water samples collected from 6 different sources in Chiang Mai, Thailand from November 2016 to July 2018 were examined for the presence of genogroups I, II, IV (GI, GII, GIV) NoVs and SaVs by using RT-nested PCR assays, genome sequencing, and phylogenetic analysis, Results: Forty out of 126 (31.7%) water samples were positive for one or more caliciviruses throughout the years of study with high prevalence in winter. Among 126 tested specimens, 34 (27.0%), 30 (23.8%), 3 (2.4%), and 2 (1.6%) were positive for NoV GI, GII, GIV, and SaV, respectively. For NoV GI, 6 different genotypes were identified with the most predominant of GI.1 genotype (17 strains). In addition, 6 different genotypes of GII were detected with high prevalence of GII.17 (12 strains) and GII.2 (11 strains). It was interesting to note that our study reported the detection of NoV GIV for the first time in water samples in Thailand, and all were GIV.1 genotype. For SaV detection, only 2 water samples were positive for SaV GI. Conclusions: The data revealed heterogeneity and highly dynamic distribution of NoV GI, GII, GIV, and SaV in environmental water in Chiang Mai, Thailand, during the study period of 2016–2018.